Three new species and new records of the genus Conocephalus Thunberg, 1815 (Orthoptera, Tettigoniidae, Conocephalinae) from Kashmir (Jammu and Kashmir), India - Shah, Muzamil Syed; Majeed, Aamir; Bashir, Ishrat; Hassan, Khalida (Zootaxa, 2025)
In Kashmir (Jammu and Kashmir), the genus Conocephalus was previously known from a single species, Conocephalus maculatus (Chandra et al., 2013). Three new species, Conocephalus usmanii sp. nov., Conocephalus nagariensis sp. nov., and Conocephalus gandebali sp. nov., are described with new records from of other species from the region. A Brief discussion concerning morphological structures and key to known Indian species of Conocephalus (Anisoptera) are provided. Also, Scanning Electron Micrographs of male stridulatory files of the new species are presented. The holotypes of new species are deposited in the Museum of Zoology Department of Aligarh Muslim University, Aligarh, India.